0.5x-(-x+3)=x-3

Simple and best practice solution for 0.5x-(-x+3)=x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.5x-(-x+3)=x-3 equation:


Simplifying
0.5x + -1(-1x + 3) = x + -3

Reorder the terms:
0.5x + -1(3 + -1x) = x + -3
0.5x + (3 * -1 + -1x * -1) = x + -3
0.5x + (-3 + 1x) = x + -3

Reorder the terms:
-3 + 0.5x + 1x = x + -3

Combine like terms: 0.5x + 1x = 1.5x
-3 + 1.5x = x + -3

Reorder the terms:
-3 + 1.5x = -3 + x

Add '3' to each side of the equation.
-3 + 3 + 1.5x = -3 + 3 + x

Combine like terms: -3 + 3 = 0
0 + 1.5x = -3 + 3 + x
1.5x = -3 + 3 + x

Combine like terms: -3 + 3 = 0
1.5x = 0 + x
1.5x = x

Solving
1.5x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
1.5x + -1x = x + -1x

Combine like terms: 1.5x + -1x = 0.5x
0.5x = x + -1x

Combine like terms: x + -1x = 0
0.5x = 0

Divide each side by '0.5'.
x = 0

Simplifying
x = 0

See similar equations:

| 3(x+1)+x^2=x^2+18 | | 2X^2=16X+8 | | 1n+20=22 | | 5(x+y)-6x=24 | | 6-2x=6x-10 | | -32q^2+72=0 | | 4cx+9y=81 | | 0.375+2.33= | | 13(h+3h)=52 | | 15.64=20.1+a(14.49) | | k^2-7k-30=0 | | -6n-20=2n+4 | | 18x-6=6x+22 | | 11x+40=6x+25 | | 24x+12x=24 | | -7(k-4)=2k-35 | | -7x-18=-4x-12 | | 4c+7=c | | 2x-(5x+4)-7=-3x+2 | | 63=3+4n-4 | | 13(h+3h)= | | -16x^2+150x+250=0 | | 7-(k-4)=2k-35 | | -40-40(2x+5)=-61 | | 18x-6=2(6x+22) | | X+(x-18)=180 | | -9x-18y=36 | | 3(-6)-y=-17 | | -20+-4x=-2(4x+-4) | | 5000=-p^2+120p+1400 | | p(0)=2.5p(1) | | 2x+40=2/11x |

Equations solver categories